Remembrance, history, and justice : coming to terms with traumatic pasts in democratic societies - Tismăneanu, Vladimir 1951- HerausgeberIn; Iacob, Bogdan C. 1979- HerausgeberIn (Central European University Press, 2015)
"The present book is a state of the art reassessment and analysis of how the interplay between memory, history, and justice generates insight that is multifariously relevant for comprehending the present and future of democracy without becoming limited to a Europe-centric framework of understanding. The volume is structured on three complementary and interconnected trajectories: the public use of history, politics of memory, and transitional justice. Subsequently, the contributors deal with trauma and the reconstitution of democratic communities, with the multiple publics of historical inquiry in the context of a shift from authoritarianism to pluralism, with the competing narratives resultant of the process of Aufarbeitung, and last but not least, with the juridical and investigative efforts to acknowledge and punish the crimes and abuses of the past. It brings together historiography with memory studies, intellectual and legal history, political analysis with theoretical insight. It integrates local and regional experiences with traumatic pasts into a global structure that offers the possibility of more general conclusions about the memory of a century touched by the 'reek of cruelty'. The authors situate the process of coming to terms with the past (communism, fascism, authoritarianism, failed democracies) in Eastern Europe (including the Western Balkans) and the former Soviet space within the larger context of discussing the memory and history of the post-war period. At the same time, the European overview is compared with other cases of post-authoritarian transitions such as those in Latin America, South Africa, Japan, and the Middle East. The result is a clustered big picture of practices of remembrance, reckoning, and historiographical reevaluation"--Provided by publisher